Dynamic modeling and simulation of waste energy harvesting system for urban car - Abdul Razak, Fadhilah; Rahman, Mohammed Ataur (Trans Tech publication, 2012)
Single cylinder engine is capable of reducing harmful emission to the environment due to reduction in fuel consumption. On the other side, supercharger is known to be able to boost air to substantially improve the fuel economy of passenger cars. However, some amount of power is required by supercharger, thus reducing the efficiency of the engine. For improving the engine efficiency, waste heat energy from coolant is transferred to the boosted air before it flows into the combustion chamber. The system which functions as heat transfer is known as Waste Energy Harvesting System (WEHS). This system has been developed in order to supply enough boosted air for creating massive turbulence effect and auto oxidation to burn 100% of fuel with very short time. WEHS will contribute to reduce power loss due to heat release from the engine as well as reduce power consumed by the supercharger.